Caracterização, patogenicidade e ação do Citral e do Mirceno sobre Colletotrichum gloeosporioides - Nicoletta Stefania Dias da Silva Flávio (2012)
The anthracnose of yellow passion fruit is caused by the Colletotrichum gloeosporioides fungus, disease which causes great losses including in the post-harvest, due to the fact of being a quiescent infection. The aim of this study was to classify and select strains of this fungus, according to the aggressiveness for further evaluation of control of this disease in vitro and in yellow passion fruits. For both was performed experiments in which were evaluated 07 (seven) isolates of C. gloeosporioides, being used speed rate parameters of mycelia growth, production of conidia, conidia size, coloring of the colony and pathogenic by means of lesion size on disks of fruits peel and production of cellulose. The data were analyzed in the program SAEG using Scott Knott test at 5% of probability. The isolates can be divided into two groups: the first, with the most aggressive isolates is composed by C94, C95 and ISO1 isolated and the second group, with C96, ISO3, ISO2 and ISO6 isolated. All the tested isolates caused injury to passion fruit. For the test of degradation of cellulose was used C95 and ISO2 isolated, being one more aggressive and less aggressive the other, respectively. Being only that the C95 isolated can degrade cellulose, thus proving the difference in the aggressiveness among isolates worked. For testing to control this disease were utilized two isolated, the C95 and ISO2, for the reasons mentioned above. It was used for the experiments testing the speed rate parameters of mycelia growth, spore production and pathogenicity by the method of disks in the skin of fruit being evaluated the citral, the myrcene and the citral more myrcene in 5 concentrations for the tests in vitro and for the pathogenicity only the myrcene in 5 different concentrations and a control with Folicur fungicide at the recommended dosage. The data were analyzed by the SAEG program by Scott Knott test at 5% of probability. For the evaluation in vitro the myrcene chemical compound showed a decrease in the rate of speed of mycelia growth, but there was not statistical difference between the concentrations measured for the isolated more aggressive and to the least aggressive from the concentration of 50% was observed growth reduction. In the production and spores of the C95 isolate, the most aggressive was observed a reduction in the number of spores from the concentration of 25%. But the fungicide tested was the best treatment, it was inhibiting the mycelial growth. In the tests for disease control in the fruits, the fungicide was not efficient, and the myrcene in concentrations of 75 and 100% reduced lesion size for the fruits inoculated with the isolate less aggressive. When it was used the more aggressive isolate there was not statistical difference between treatments. The conclusion of this study was that the myrcene showed a reduction in lesion size in passion fruits and in vitro on the mycelial growth, but when it used a less aggressive isolated.